Key Characteristics and Components of Cloud Computing - Mr. Dharmesh Dhabliya, Mrs. Ritika Dhabliya (International Journal of Control and Automation, 2019)
The utilization of cloud computing has expanded quickly in numerous associations. Cloud provider should address protection and security issues as an issue of high and dire need. This paper centers on the key characteristics, components and data security. As data and data will be imparted to an outsider, cloud computing clients need to maintain a strategic distance from an untrusted cloud provider. Cloud computing gives a proficient, scalable, and cost- effective way for the present associations to convey business or customer IT services over the web. The adaptability and transparency of cloud computing models have made various security concerns. Right now, describe the issues and their effect on appropriation.